The Quality of Frozen Semen Sexing with Percoll Medium and Bovine Serum Albumin (BSA) in Dorper Sheep and Saanen Goat - Sumaryadi Mas Y.; Pangestu Mulyoto; Hidayah Chomsiatun N.; Nugraha Aras P.; Saleh Dadang Mulyadi; Sugiarto Mochammad (E3S Web of Conferences)
The study aimed to determine the quality of frozen semen sexing with percoll medium and Bovine Serum Albumin (BSA) in Dorper sheep and Saanen goats. The research was designed based on the experimental method, as the main plot is livestock (M) consisting of two levels, namely M1 (Dorper sheep) and M2 (Saanen goats), while as a sub plot is sex separation medium (S) consisting of percoll medium (S1) and BSA medium (S2), each treatment combination was repeated 3 (three) in the form of semen collection. The results of analysis of variance showed that the quality of unsexed semen in sample and separation medium did not show significant differences (P>0.05). It means that the quality of unsexing semen in Dorper sheep and Saanen goats both using percoll medium and BSA was relatively the same. The results showed a decrease in the quality of spermatozoa Y from post-thawing sexing frozen semen compared to the quality of fresh semen unsexing in Dorper sheep for motility, viability, concentration respectively by 16.55; 4.52; and 20.34% and an increase in abnormality of 103.37% compared to fresh semen unsexing. While in Saanen goats there was a decrease in the quality of X spermatozoa from post-thawing sexed frozen semen compared to the quality of fresh unsexed semen for motility, viability, concentration of 19.23; 21.91; and 17.08%, respectively, and an increase in abnormality of 110.52%. However, the quality of sexed frozen semen in Dorper sheep and Saanen goats was still within the limits that can be used for artificial insemination programs. It can be concluded that to obtain Y spermatozoa in Dorper sheep, and X spermatozoa in Saanen goats using 45:60% percoll medium and 5:15% BSA medium separation.